Analisis Faktor-Faktor Yang Mempengaruhi Kesejahteraan Masyarakat di Provinsi Riau Tahun 2008-2017 - Wiwin Indrayanti* (LPPM Universitas BSI, 2020)
ABSTRACTThe level of welfare that has a fluctuating trend with a downward trend, will have an impact on the reduced ability of the community to meet their needs, so that will affect their welfare. This study aims to analyze the factors that affect the welfare of the people in Riau Province. The variables used in this study include the level of poverty, the level of open unemployment (TPT), per capita expenditure, and economic growth. The method used panel data regression that uses secondary data sources obtained from the Central Statistics Agency (BPS) in 2008-2017. The sampling technique used is sampling saturated with data in 11 districts and cities in Riau Province. The results showed that the poverty rate has a negative effect and per capita expenditure has a positive effect on community welfare, while the unemployment and growth rates do not significantly affect on community welfare. Reform of government policies in the economic sector needs to be done to prevent or reduce poverty and unemployment, and create development programs towards a prosperous society.Keywords: community welfare, poverty, TPT, per capita expenditure, GRDP